HUBUNGAN POLA ASUH ORANG TUA DENGAN LAMA PENGGUNAAN GADGET PADA ANAK PRASEKOLAH - Ni Kadek Diah Ari Anggreni; I Komang Lindayani; Ni Nyoman Budiani (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2021)
Gadget can affect children’s development and social interaction. Parenting has important role to limit gadget used for the children. The purpose of this research was to know the relationship between parenting with the length of gadget used for preschool children. This study used analytic correlation with cross-sectional method. This study was done in Kindergarten of Sila Chandra III which located in Batubulan, Sukawati, Gianyar regency. Sampel of this research was 60 which already fulfilled the inclusion criteria. This research used non-probability sampling with concecutive sampling method. The data obtained from the questionnaire. The technique of data analysis was bivariate analysis used alternative Fisher Exact Test. The result of this research showed that democratic parenting was 88.3%, permissive was 6.7%, authoritarian was 5.0%, the gadget use not long length was 81.7%, and the long length use was 18.3%. In addition, the result of fisher exact test was p=0.017 (p0.05) PR authoritarian= 3.286 and Gadget can affect children’s development and social interaction. Parenting has important role to limit gadget used for the children. The purpose of this research was to know the relationship between parenting with the length of gadget used for preschool children. This study used analytic correlation with cross-sectional method. This study was done in Kindergarten of Sila Chandra III which located in Batubulan, Sukawati, Gianyar regency. Sampel of this research was 60 which already fulfilled the inclusion criteria. This research used non-probability sampling with concecutive sampling method. The data obtained from the questionnaire. The technique of data analysis was bivariate analysis used alternative Fisher Exact Test. The result of this research showed that democratic parenting was 88.3%, permissive was 6.7%, authoritarian was 5.0%, the gadget use not long length was 81.7%, and the long length use was 18.3%. In addition, the result of fisher exact test was p=0.017 (p0.05) PR authoritarian= 3.286 and PR permissive= 19.714, showed that there is a significant relationship between parenting with the length of gadget use in children preschool. Sugestion for the next research is to analysis other factors that affect the length of gadget used.